Performance evaluation of continuous production lines with machines having different processing times and multiple failure modes - Levantesi, R.; Matta, A.; Tolio, T. (Performance evaluation, 2003)
This paper presents an approximate analytical method for the performance evaluation of asynchronous production lines with deterministic processing times, multiple failure modes and finite buffer capacity. The discrete flow of parts is approximated by a continuous flow of material. The technique developed here is based on the approximate evaluation of a K machine line by the evaluation of K−1 two-machine lines: unlike previous work on this subject, the multiple failure approach allows to consider real and virtual failure modes for each building block in which the original line is decomposed. Indeed, to reproduce in each two-machine lines the flow of material observed in the related buffer of the original line, real failures are used to take into account the reliability of the physical machines while virtual failures are introduced to model the different interruptions of flow that can arise inside the line thus preventing machines from working. To assess the accuracy of the proposed method, extensive simulation and numerical experiments have been carried out.